Collaborative work a challenge in teacher training - Aliaga Cruz, Rosaelvira (2022)
Currently, teacher training demands more flexible, active and participatory teaching proposals, adapted to the needs and characteristics of 21st century students, aimed at developing a set of skills and abilities that respond to a profile that allows them to face the demands social and labor. In this sense, one of the strategies that responds to this is collaborative work that allows them to assume responsibility for their learning, reflect on their cognitive processes and develop knowledge of different complexity. In this context, the objective of this research was to conceptually review what is referred to as collaborative work, as well as its contributions and challenges in teacher training. To this end, the literature on the subject proposed in recent years has been reviewed and analyzed through an exploratory-descriptive methodology. The findings allow us to highlight that teacher training requires the interaction of each other by sharing knowledge, resolving conflicts and solving problems, being tolerant and respectful of others, as well as having greater autonomy and control over the assigned task. Likewise, they require the teacher to know the fundamentals and methodology of collaborative work to propose academic tasks and thus guarantee the expected learning, as well as the expected profile.